Longer term patient management following stroke: A systematic review. Issue 8 (October 2021) - Boehme, Christian; Toell, Thomas; Lang, Wilfried; Knoflach, Michael; Kiechl, Stefan
Background: Tremendous progress in acute stroke therapy has improved short-term outcome but part of this achievement may be lost in the long run. Concepts for a better long-term management of stroke survivors are needed to address their unmet needs and to reduce the burden of post-stroke complications, residual deficits, and recurrent vascular events. Aims: This review summarizes current knowledge on post-hospital care and the scientific evidence supporting individual programs. Summary of review: A systematic search of electronic databases according to PRISMA guidelines identified 10, 374 articles, 77 of which met the inclusion criteria. One large randomised controlled trial on a multifaceted care program delivered by the multidisciplinary stroke team reduced recurrent vascular events and improved quality of life and functional outcome one year after the event, while a number of studies offer solutions for individual components of post-hospital disease management like patient education, counselling, and self-management or the management of post-stroke complications and residual deficits. A majority of studies, however, was small in size and limited by a short follow-up. Most initiatives with a narrow focus on risk factor control failed to lower the risk of recurrent events. The caregivers' central role in post-stroke patient management is broadly neglected in research. Conclusions: Over the past years, first knowledge on how to best organize post-hospital care of stroke patients has emerged. Comprehensive and pragmatic programs operated by the multidisciplinary stroke team hold promise to reduce the long-term health burden of stroke. There is a clear need for further high-quality studies with both clinical endpoints and patient-reported outcomes to establish sustainable solutions in different settings and regions to improve life after stroke, a key priority of the Stroke Action Plan for Europe 2018–2030.